Use of Coils in Conjunction With the Pipeline Embolization Device for Treatment of Intracranial Aneurysms. Issue 2 (February 2015) - Lin, Ning; Brouillard, Adam M.; Krishna, Chandan; Mokin, Maxim; Natarajan, Sabareesh K.; Sonig, Ashish; Snyder, Kenneth V.; Levy, Elad I.; Siddiqui, Adnan H.
Abstract : BACKGROUND: Coiling in conjunction with Pipeline embolization device (PED) placement could provide immediate dome protection and an intraaneurysmal scaffold to prevent device prolapse for intracranial aneurysms with high rupture risk and complex anatomy. OBJECTIVE: To report results after treatment of aneurysms with PED with coils (PED+coils group) or without (PED-only group) at a single-institution. METHODS: In this case-controlled study, records of patients who underwent PED treatment between 2011 and 2013 were retrospectively reviewed. RESULTS: Twenty-nine patients were treated with PED+coils and 75 with PED-only. No statistically significant between-group differences were found in terms of age, sex, aneurysm location, medical comorbidities, and length of follow-up. Aneurysms treated by PED+coils were larger (16.3 mm vs 12.4 mm, P = .02) and more likely to be ruptured (20.7% vs 1.3%, P = .001) or dissecting (34.5% vs 9.3%, P = .002). PED deployment was successful in all cases. At the latest follow-up (mean, 7.8 months), complete aneurysm occlusion was achieved in a higher proportion of the PED+coils group (93.1% vs 74.7%, P = .03). Device foreshortening/migration occurred in 4 patients in the PED-only group and none in the PED+coils group. Fewer patients required retreatment in the PED+coils group (3.4% vs 16.0%, P = .71). Rates of neurological complications (10.3% PED+coils vs 8.0% PED-only, P = .7) and favorable outcome (modified Rankin Scale score = 0-2; 93.1% PED+coils vs 94.7% PED-only, P = .6) were similar. CONCLUSION: PED+coils may be a safe and effective treatment for aneurysms with high risk of rupture (or rerupture) and complex anatomy. Coiling in conjunction with PED placement provided a higher aneurysm occlusion rate and reduced the need for retreatment. ABBREVIATIONS: CI, confidence interval ICA, internal carotid artery mRS, modified Rankin Scale PED, Pipeline embolization device OR, odds ratio